Obszary samodzielności gmin - Lubimow-Burzyńska, Iwona (The Areas of Independence of the Commune, 2007)
The Independence of the commune issue is often considered by many authors focusing on the finances of local government. In this article the problem is narrowed down to two aspects: the decision making independence of the commune institutions and financial independence of the commune itself. The areas of self determining and legal barriers of commune independence are also described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 289-299